Development of Android-Based Project-Based Learning Media to Enhance Students Enterpreneurial Skills - Siti Suprihatin; Sangidatus Sholiha; Ira Vahlia (AL-ISHLAH: Jurnal Pendidikan, 2025)
Entrepreneurship education at the higher education level often faces challenges in bridging theoretical knowledge with practical application. Students frequently lack the necessary skills to implement entrepreneurial concepts in real-life contexts. This study aimed to develop an Android-based learning media using a Project-Based Learning (PjBL) approach to enhance students' entrepreneurial skills. The study employed a Research and Development (RD) method using the ADDIE model, which includes five phases: Analysis, Design, Development, Implementation, and Evaluation. The product was evaluated through expert validation (content and media), small and large group practicality tests, and effectiveness testing using the N-Gain formula. The developed learning media was rated as very valid by experts, with a material validation score of 90.6 and a media validation score of 77.9. The practicality test showed a high level of usability with an average score of 80.45%, categorized as very practical. The effectiveness test produced an N-Gain score of 0.5788, indicating a moderate level of effectiveness in improving entrepreneurial skills. The findings suggest that the Android-based PjBL learning media effectively supports students in understanding and applying entrepreneurial concepts through real-world projects. Its integration of mobile technology with experiential learning offers a flexible and engaging alternative to conventional instruction. This study contributes an innovative, technology-integrated instructional model that enhances entrepreneurship education by fostering practical skill development among university students in the digital era.